Seven Standards of Textuality in Parents-Child Communication in An English Movie (A Discourse Study) - Rashid Juma'a, Taqwa (Journal of College of Education, 2019)
Any text whether written or spoken  should meet several standards in order to have communicative qualities, on such a basis the current study is set out. However, the current study is an endeavor to study the textuality communication between parents and their children in an English movie which is "Wonder"  by adopting Robert De Beaugrande’s and Wolfgang U. Dressler’s 1981  Seven Standards of Textuality. The main goal of the study is to examine the applicability of these standards to such a  type of spoken sample which is movie communication as the previous studies focused only on the written ones. Finally, the study shows that textuality is the main means of the text-processing since  the seven standards of textuality are handled through data analysis. In terms of seven standards found in selected movies, it is displayed that all standards are found and explored when cohesion, coherence and intertexuality top the list of the most frequent occurrences whereas informativity standard is less frequent one.